Thimbles : a novel - Wiseman, David (Boston : Houghton Mifflin, 1982)
A twentieth-century girl is magically transported through time to join the 1819 demonstration which ended in tragedy for Manchester mill workers seeking the right to vote.
Keywords: Civil rights -- Fiction; Time travel -- Fiction; Peterloo Massacre, Manchester, England, 1819 -- Fiction; Manchester (England) -- Fiction; England -- Fiction